Exploring agrodiversity - Brookfield, H. C. (Issues, cases, and methods in biodiversity conservation., 2001)
Small farmers are often viewed as engaging in wasteful practices that wreak ecological havoc. Exploring Agrodiversity sets the record straight: Small farmers are in fact ingenious and inventive and engage in a diverse range of land-management strategies, many of them resourcefully geared toward conserving resources, especially soil. They have shown considerable resilience in the face of major onslaughts against their way of life by outsiders and government. Using case studies from Africa, Asia, Latin America, and the Pacific, this book provides in-depth analysis of agricultural div.